Autologous Transfusion after Total Knee Arthroplasty - Fayyaz Ahmed Orfi; Hussain, Shafqat; Dilbar, Ramna; Munir, Ali Arslan; Sumbal Rana (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine whether the blood lost in total knee arthroplasty surgery can be salvaged and reused using the autotransfusion technique without adverse effects and need more blood requirement. Study Design: Prospective longitudinal study.Place and Duration of Study: Department of Orthopaedic Surgery, Combined Military Hospital Rawalpindi from Aug 2020 to Dec 2021.Methodology: The study included all the candidates undergoing total knee replacement surgery. Fifty-five patients underwent autologous transfusion using blood bags attached to drains and reusing them within 4-6 hours. All the transfusions were recorded.Results: Out of 55 patients, 49(89%) underwent unilateral knee replacement, and 6(11%) underwent bilateral knee replacement. All 49 patients (89%) received a single blood transfusion, and all 6(11%) bilateral knee replacements received two blood transfusions each. Out of 61 transfusions, no adverse reaction was noted. One patient needed additional blood transfusion while undergoing bilateral knee replacement.Conclusion: Blood autologous transfusion during knee replacement surgeries is a practical and cost-effective measure, especially in rare blood groups. Autotransfusion is a simple and hassle-free approach that can be used routinely while avoiding adverse blood reactions.